Why Hasn't Indonesia Ratified The Hague System? What's The Problem? - Mohammad Reza Fachruddin; Dewi Sulistianingsih; Rodiyah; Fakhrana Nabila Atiqawati; Lisa Amalia (Universitas Negeri Semarang, 2026)
Despite its membership in key international intellectual property (IP) agreements, Indonesia has not yet acceded to the Hague System for the International Registration of Industrial Designs. This article employs a doctrinal, principle-based legal analysis to examine the alignment of Indonesia’s industrial design regime, particularly Law No. 31 of 2000, with international standards under the TRIPS Agreement, the Paris Convention, and the Geneva Act of 1999. The study analyses statutory provisions, international instruments, and case law, and is complemented by a comparative overview of jurisdictions such as Japan, Singapore, the Republic of Korea, and Viet Nam that have already joined the Hague System. The findings reveal persistent structural issues in the Indonesian framework, including ambiguity in the novelty requirement, overlapping protection between industrial designs, copyright, and three-dimensional trademarks, as well as limited substantive examination and territorial fragmentation of protection. These legal and administrative constraints hinder the effective use of an international registration system, even though the Hague System offers procedural efficiency, cost reduction, and broader market access for designers. The article argues that targeted legislative reform and regulatory harmonization are essential preconditions for accession and contends that such reforms would enhance legal certainty, strengthen design protection, and improve Indonesia’s competitiveness in the global creative economy.